Stem Cell-Derived Hepatocyte-Like Cells as Model for Viral Hepatitis Research - Jingjing Wang; Bingqian Qu; Fang Zhang; Cindy Zhang; Wanyan Deng; Viet Loan Dao Thi; Yuchen Xia (Stem Cells International)
Viral hepatitis, the leading cause of liver diseases worldwide, is induced upon infection with hepatotropic viruses, including hepatitis A, B, C, D, and E virus. Due to their obligate intracellular lifestyles, culture systems for efficient viral replication are vital. Although basic and translational research on viral hepatitis has been performed for many years, conventional hepatocellular culture systems are not optimal. These studies have greatly benefited from recent efforts on improving cell culture models for virus replication and infection studies. Here we summarize the use of human stem cell-derived hepatocyte-like cells for hepatotropic virus infection studies, including the dissection of virus-host interactions and virus-induced pathogenesis as well as the identification and validation of novel antiviral agents.